THU0185 Reliability of ra mri scoring. (1st June 2001) - Lassere, MN; McQueen, F; Ostergaard, M; Conaghan, P; Shnier, R; Peterfy, C; Klarlund, M; Stewart, N; O'Connor, P; Bird, P; Edmonds, J; Emery, P; et al.
Abstract : Background: At OMERACT5 recommendations were developed for acquisitions/scoring of MRI synovitis/bone destruction of hand/wrist in RA: OM5 RA MRI Score (Om5 RAMRIS). 1 These were based on results of a multicentre inter-reader agreement studies of two earlier MRI scoring methods, developed at EULAR 1999 and ACR 1999. 2 Objectives: Determine whether reader calibration, standardisation of imaging protocols and more precise definitions of lesions improved inter-reader agreement of MRI scoring. Methods: MRIs (1.5T, cor and axial T1& T2, FS, iv Gd) of wrist (8)& 2‑5 MCPJ(10) scored by experienced readers in 5 centres. Synovitis determined by Gd enhancement in synovial compartment by 2 methods: global score (0‑3)(wrist 3 sites, MCPJ 4 sites) and direct measure (mm) of maximal thickness of enhancing tissue (wrist 4 sites, MCPJ 2 sites). Bone erosion (wrist 15 sites, MCPJ 8 sites) was a bone defect with sharp margins, with a cortical break. Bone defect and bone oedema also defined. All measured 0‑10 by volume of defect as proportion of assessed bone volume by 10% increments judged on all images. Results: Reliability for most sites for all lesions was good. Poor intraclass correlation coefficients for bone defect (but excellent agreement) were due to predominance of zero scores. Table 1 shows results of summated scores). Om5 RAMRIS performed better than our previous scoring methods. Conclusion: We found Om5 RAMRIS has acceptable inter-reader reliability. Whether it can be further improved and degree to which it's sensitive to change will need to be determined by its performance in longitudinal/intervention studies. References: Conaghan, et al . J Rheum, in press Ostergaard, et al . J Rheum, in press